Pengaruh Prinsip Tata Kelola Organisasi Terhadap Kecenderungan Korupsi Pada Bumdes Dengan Moralitas Individu Sebagai Variabel Moderasi - Dimas, Putu Pastika; Prayudi, Made Aristia (Vokasi : Jurnal Riset Akuntansi, 2025)
Effective governance can suppress the tendency of corruption, but its implementation at the village level still faces various obstacles. This results in significant misappropriation of funds. This study aims to determine the effect of organizational governance principles on the tendency of corruption in BUMDes with individual morality as a moderating variable. This study uses a quantitative method with a population of 150 BUMDes administrators in Klungkung Regency. The research sample consisted of 126 respondents selected using the Simple random sampling technique with the Slovin formula. Data collection through questionnaires was analyzed using descriptive tests, data quality tests, classical assumption tests, simple linear regression analysis, and hypothesis testing with the help of SPSS 25. The results of the study indicate that the principles of cooperative, participatory, emancipatory, transparent, accountable, and sustainable governance have a negative and significant effect on the tendency of corruption, individual morality negatively moderates the principles of cooperative, participatory, emancipatory, and sustainable governance on the tendency of corruption, individual morality positively moderates the principles of transparent, and accountable governance on the tendency of corruption.